1992
DOI: 10.1515/znc-1992-11-1206
|View full text |Cite
|
Sign up to set email alerts
|

Isoflavone And Pterocarpan Malonylglucosides And ß - L,3 - Glucan - And Chitin-Hydrolases Are Vacuolar Constituents In Chickpea (Cicer Arietinum L.)

Abstract: Cell suspension cultures of chickpea (Cicer arietinum L.) were used to prepare protoplasts and vacuoles. The vacuolar preparation revealed only slight contaminations of cytoplasmic marker enzymes. H PLC analysis of the vacuolar extract showed that the malonylglucosides of isoflavones, isoflavanones and pterocarpans are exclusively located in the vacuole. Experi ments designed to determine the subcellular localization of the isoflavone malonylglucoside: malonylesterase suggest an association of this enzyme with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…This ABCtype transporter also seems to be specific to isoflavones as transport substrates because all isoflavones tested inhibited genistein transport in the competition assay, whereas flavanone and flavonol do not seem to be recognized by the transporter protein (Table II). In plants, flavonoids often accumulate as the glucoside forms and the transport of flavonoid glucosides into vacuoles has also been reported (Mackenbrock et al, 1992;Klein et al, 1996;Frangne et al, 2002), but the transport of flavonoid aglycones at the plant plasma membrane has not been biochemically characterized thus far, except for this study. .…”
Section: Discussionmentioning
confidence: 94%
“…This ABCtype transporter also seems to be specific to isoflavones as transport substrates because all isoflavones tested inhibited genistein transport in the competition assay, whereas flavanone and flavonol do not seem to be recognized by the transporter protein (Table II). In plants, flavonoids often accumulate as the glucoside forms and the transport of flavonoid glucosides into vacuoles has also been reported (Mackenbrock et al, 1992;Klein et al, 1996;Frangne et al, 2002), but the transport of flavonoid aglycones at the plant plasma membrane has not been biochemically characterized thus far, except for this study. .…”
Section: Discussionmentioning
confidence: 94%
“…Based on either confocal microscopy or computational prediction, G2, G3, and G4 are localized to either vacuole or cytosol. The isoflavone conjugates of chickpea cell suspension cultures are vacuolar localized (37), and these compounds were found in the soluble fraction (cytoplasmic plus vacuolar contents) in Medicago. Cell fractionation studies suggested that chickpea isoflavone glucosidase activity was primarily cytoplasmic, whereas the malonylesterase activity responsible for the initial degradation of isoflavone-7-O-glucoside-6ЈЈ-malonate (38) was associated with the vacuolar membrane (37).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, isoflavone glycosides are hydrolyzed to their aglycones by lactobacilli, Bacteroides and Bifidobacteria in the intestinal flora, and by lactase phlorizin hydrolase in the small intestinal brush border cells (43). Glycosylation may be a favorable trait for engineered isoflavonoid nutraceuticals, as it results in their storage in the vacuole (44), away from further potential metabolism.…”
Section: Ifs Expression Affects Flavonol and Anthocyanin Biosynthesismentioning
confidence: 99%